(3TQM MeGSI CHj JeGes - (3jMji Hf Ydj Hf GdMSf Hf ehSi Hf HSWGe GdNWjH GdJHQjRj GddZhj , CHh RcQjG , J (B502 (3g` s; (3CHh JeGe GdWGFj , CHh JeGe MHjH Hf ChS Hf GdMGQK GdWGFj,J (B231 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO ddg GdPi dG jHdZ UaGJg GdhUGahf , hdG jOQc jbjfg GdYGQahf aEf Cgd GdCOH jJHGjfhf Hg ai OQLGJge s
(3BNQgG (B:s
(3MeOJ Gdgi HYO YQhI EP fLG NQGT, hHYV GdTQ Cghf ef HYV hGdMeO ddg s
(3GdTQM GdeJhSW LRAGf ai eLdOs
(3GfXQ GjVG GdLRA GdChd GOH Qbe (B519 (3COHs
(3HChdgG BKGQ QWhHg hJQajYs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs